VD_FINDINFO AI 426/10 - 5/2012 vom 28. Oktober 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, NOUVELLE DEMANDE, DEGRÉ DE L'INVALIDITÉ | 28 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 87 al. 3 RAI, 87 al. 4 RAI